مبدأ الإختصاص العالمي ودوره في تحقيق العدالة الجنائية وقمع إنتهاكات القانون الدولي الانساني - حمادي, خالد عواد (Journal of Legal Sciences, 2017)
As the armed struggles grew on the international and national levels and due to the widespread violations of Humanitarian International Law, an urgent need emerged to search for mechanisms that to be just with the victims and restrain the criminals for achieving the Criminal Justice. We can say that adopting the international criminal specialization, in which specialization for countries' national courts are held for pursuing the violators regardless of place of their occurrence,  or criminal's or victim's nationality, could contribute into these requirements.Judging on the effectiveness of the principle in achieving the desired goal requires knowing how far it could be dedicated in the framework of Humanitarian International Law and the excuses of relaying on it, and if there are juridical precedents it based on, and if it is far from the difficulties and obstacles that might obstruct him. These are what this study is trying to clarify in a way that falls in the interest of our target.